Relaciones hipertextuales en la primera etapa de Rodolf Sirera (1969–1977) - Ramon X. Rosselló (Interlitteraria)
In the article titled Hypertextual Relations in the First Phase of Rodolf Sirera’s Career (1969–1977), our object of study will be the plays composed by Rodolf Sirera (born Valencia, 1948) during the first phase of his career, between 1969 and 1977. Sirera is one of the most notable dramatists writing in Catalan, beginning his career with an involvement in what was then called ‘independent theatre’ as a member of groups like the Centre Experimental de Teatre and El Rogle. We will begin by reviewing the prominent role played by transformative hypertextual relationships during this early period in the composition of his dramatic texts, which were mainly based on hypotexts of Valencian origin. Secondly, we will discuss the relationship of Sirera’s writing with epic theatre, one of the dramatic genres that had the most significant impact on dramaturgy in Spain in the second half of the 1960s and early part of the 1970s. Finally, analysis of these two types of hypertextual relationship will allow us to distinguish two distinct points in the development of this first period, since from 1974 onwards we can observe a gradual abandonment of hypertextual practices in favour of original fiction with a lesser presence of Brechtian devices.